Chemical Constituents from Chloranthus elatior and Their Inhibitory Effect on Human Dihydroorotate Dehydrogenase - Yang, Qian; Jia, An; Liu, Xizi; Han, Shiyi; Fan, Siyang (Planta Medica, 2021)
A new sesquiterpene, chlorantholide G (1), a new sesquiterpene dimer, elatiolactone (2), and 2 new diterpenes, elatiorlabdane B (3) and elatiorlabdane C (4), together with 51 known compounds, were isolated from the aerial parts of Chloranthus elatior. The new structures including their absolute configurations were mainly established by mass spectrometric, NMR, and electronic circular dichroism experiments. All isolated compounds were tested for their anti-hDHODH activity. (4S,6R)-4-hydroxy-6-isopropyl-3-methylcyclohex-2-enone (5) and (4S,5R,9S,10R)-8(17),12,14-labdatrien-18-oic acid (29) were the most active compounds with IC50 values of 18.7 and 30.7 µM, respectively.
Keywords: Chloranthus elatior; Chloranthaceae; sesquiterpenes; sesquiterpene dimers; diterpenes; hDHODH inhibition